Beyond Slow: The Problem of Realism in Contemporary Minimalist Cinema - McGrath, Sean Kenta (Curtin University, 2014)
This thesis examines how a series of contemporary narrative filmmakers use minimalism paradoxically to enhance, detract from and interrogate the realism of their films, in order to critique current cinematic practices and investigate new approaches to the centuries-old dilemma of how reality can be represented on screen. This thesis is a creative doctoral project, comprising of an exegesis and a feature-length documentary/fiction film, This Used To Be Here.